Community Service Introduction To Innovation During Dimasa Orba To Improve The Nutrition Of Pregnant Women in the KEK Village in Mekargalih - Lisa Trina Arlym; Tresnasari, Rubianti Dewi; Elis Sri Mulyati; Rini Andriani; Siesca Sundari; Karsini; In In Siti Hindun; Utari Kusuma Wardani; Ai Hartini (International Journal of Community Services, 2025)
Abstract Background: Government efforts to improve family health include improving family nutrition. One of the solutions to overcome nutritional problems is to hold a nutritional improvement program by utilizing local food ingredients called Local PMT. The provision of local PMT is intended for toddlers and pregnant women who experience chronic energy deficiency. Based on the results of a preliminary survey in Mekargalih Village, Tarogong Kidul District, Garut Regency, the prevalence of KEK in pregnant women in November was 20.75%, where the RPJMN target in 2024 was 10%. Of the 53 pregnant women, 11 pregnant women experienced KEK. KEK is a condition where a person suffers from an imbalance in nutritional intake (energy and protein) that lasts for years. Pregnant women who experience KEK will have problems during pregnancy, childbirth and postpartum. In addition, it will also have an impact on fetal development. The government has made efforts to help reduce the incidence of KEK in pregnant women by providing additional food regularly to pregnant women, but these efforts have not been able to achieve the expected target. Objective: The implementation of community service is to empower the community by increasing the knowledge of pregnant women, cadres and community leaders about the impact of KEK on pregnant women and teaching pregnant women with KEK skills in processing varied and innovative foods. Method: The method used in this study was to provide counseling on the impact of malnutrition on toddlers and introduce the DIMASA ORBA innovation. Participants in this activity were 11 pregnant women who experienced KEK, Posyandu cadres, and community leaders. Conclusion: This activity began with a preliminary survey, conducting a Forum Discussion Group (FGD) to determine the priority of problems and interventions to be given. The implementation of the intervention was assessed by pre-test and post-test to see the effectiveness of the counseling provided. The evaluation results showed that there was an increase in knowledge in pregnant women with an average value of the pre-test results of 55.45 and the post-test results of 93.63. So it can be concluded that pregnant women understand the impact of KEK during pregnancy. We hope that pregnant women can meet their nutritional intake during pregnancy by consuming foods that are high in calories and protein, in accordance with the innovation provided, namely DIMASA ORBA, an abbreviation of chicken, carrot and spinach dimsum. Keywords: DIMASA ORBA, Pregnant Women, KEK